A study of turn-yelding cues in human-computer dialogue - Gravano, Agustín (2014)
Previous research has made signi cant advances in under- standing how humans manage to engage in smooth, well-coordinated conversation, and have unveiled the existence of several turn-yielding cues | lexico-syntactic, prosodic and acoustic events that may serve as predictors of conversational turn nality. These results have subse- quently aided the re nement of turn-taking pro ciency of spoken dia- logue systems. In this study, we nd empirical evidence in a corpus of human-computer dialogues that human users produce the same kinds of turn-yielding cues that have been observed in human-human interac- tions. We also show that a linear relation holds between the number of individual cues conjointly displayed and the likelihood of a turn switch.